2020
DOI: 10.1017/ice.2020.281
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing antimicrobial stewardship tools in the electronic medical record for the management of COVID-19 patients

Abstract: During the COVID-19 pandemic, the antimicrobial stewardship module in our electronic medical record was reconfigured for the management of COVID-19 patients. This change allowed our subspecialist providers to review charts quickly to optimize potential therapy and management during the patient surge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…15 Similarly, 2 other ASPs utilized flags and other EHR tools to identify which COVID-19 patients would most benefit from ID consultation, a resource that became increasingly strained as hospital censuses rapidly increased. 21,22 The severe morbidity and mortality seen in COVID-19 patients prompted an unprecedented use of antimicrobial agents, both within and outside clinical trials. Given the initial limited supply of medications thought to show antiviral activity against SARS-CoV-2 and uncertainty around which patients would benefit the most from their use, ASP teams applied their expertise to the development of COVID-19 therapeutic guidelines, and they helped allocate these limited resources.…”
Section: Impact Of Asps On the Covid-19 Pandemicmentioning
confidence: 99%
“…15 Similarly, 2 other ASPs utilized flags and other EHR tools to identify which COVID-19 patients would most benefit from ID consultation, a resource that became increasingly strained as hospital censuses rapidly increased. 21,22 The severe morbidity and mortality seen in COVID-19 patients prompted an unprecedented use of antimicrobial agents, both within and outside clinical trials. Given the initial limited supply of medications thought to show antiviral activity against SARS-CoV-2 and uncertainty around which patients would benefit the most from their use, ASP teams applied their expertise to the development of COVID-19 therapeutic guidelines, and they helped allocate these limited resources.…”
Section: Impact Of Asps On the Covid-19 Pandemicmentioning
confidence: 99%
“…Three research domains identified below (Supplemental Table 4) represent priority areas with unanswered questions concerning antimicrobial stewardship in healthcare settings: presumptively receive antibiotics to treat the potential that the infection is bacterial or that a superimposed bacterial infection is leading to a greater severity of COVID-19. [93][94][95] Similarly, changes in the volume of healthcare access (decreased hospitalizations and outpatient visits) during the pandemic will limit longitudinal comparisons due to altered denominators for typical use metrics, patient bed-days of care (for acute care) and in-person visits (for outpatient care).…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%
“…Although a decrease in the number of admitted patients may lead to a reduction in overall antimicrobial use, several studies have suggested a large percentage of COVID-19 patients presumptively receive antibiotics to treat the potential that the infection is bacterial or that a superimposed bacterial infection is leading to a greater severity of COVID-19. [93][94][95] Similarly, changes in the volume of healthcare access (decreased hospitalizations and outpatient visits) during the pandemic will limit longitudinal comparisons due to altered denominators for typical use metrics, patient bed days of care (for acute care), and in-person visits (for outpatient care). Additionally, with routine pediatric care transitioning to predominantly telehealth visits, the pandemic's impact on outpatient antibiotic prescribing practices for children remain unexamined (Supplementary Table 5 online).…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%
“… 7 , 10 , 11 The established overuse of antimicrobials in this patient population emphasizes the need for antimicrobial stewardship intervention, and application of fundamental stewardship strategies to patients with COVID-19 have been previously described. 12–17 …”
Section: Introductionmentioning
confidence: 99%